PELATIHAN DAN SOSIALISASI PLATFORM EDMODO KEPADA GURU SMA NEGERI 1 DEMON PAGONG FLORES TIMUR DI MASA PANDEMI COVID-19 - Lukas Pardosi; Desta Gloria Siahaan (Fakultas Teknik, Universitas Bangka Belitung, 2022)
Abstract One of the e-learning platforms that can be used during the Covid-19 pandemic is Edmodo. Edmodo learning media which is very functional, besides being able to be used for students and lecturers, can also be used by parents. Assignments are given through the assignment and quiz features that have a time limit, so they can practice discipline in doing assignments. The purposes of implementing this activity are; First, to provide concepts and socialization of the use of Edmodo for the learning process. Second, to provide knowledge about how to use and apply the features contained in the Edmodo platform to facilitate the learning process. The targets for this service are teachers at SMA Negeri 1 Demon Pagong, East Flores. This service is expected to be able to provide additional skills for teachers how to use the e-learning platform (edmodo) for free to support conventional learning during this covid-19 pandemic. This activity lasted for one day by using Zoom.